Posttransplant Lymphoproliferative Disorder after Cardiac Transplantation in Children: Life Threatening Complications Associated with Chemotherapy Combined with Rituximab. (17th June 2013) - Fukushima, Norihide
Abstract : Despite the excellent long-term survival currently achieved in pediatric heart transplant recipients, posttransplant lymphoproliferative disorders (PTLDs) are one of the most important causes of morbidity and mortality after heart transplantation (HTx), especially in children. Timely and accurate diagnosis based on histological examination of biopsy tissue is essential for early intervention for PTLD. Chemotherapy is indicated for patients with poor response to reduction of immunosuppressive medication and for highly aggressive monomorphic PTLD. The use of rituximab in combination with chemotherapy is effective to suppress B cell type PTLD (B-PTLD). However, PTLD relapses frequently and the outcome is still poor. Although everolimus (EVL) has been reported to inhibit growth of human Epstein-Barr-virus- (EBV-) transformed B lymphocytes in vitro and in vivo, EVL has several side effects, such as delayed wound healing and an increase in bacterial infection. During combined treatment of chemotherapy and rituximab, B-PTLDs are sometimes associated with life-threatening complications, such as intestinal perforation and cardiogenic shock due to cytokine release syndrome. In HTx children especially treated with EVL, stoma should be made to avoid reoperation or sepsis in case of intestinal perforation. In cases with cardiac graft dysfunction possibly due to cytokine release syndrome by chemotherapy with rituximab for PTLD, plasma exchange is effective to restore cardiac function and to rescue the patients.